2020
DOI: 10.1002/advs.201903544
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Crystallization and Melting Pathways in the Free‐Energy Landscape of a Au–Si Eutectic Alloy

Abstract: Crystals do eventually melt if they are heated to their characteristic melting point. However, this is practically only the case for high‐temperature stable crystals, whereas low‐temperature metastable crystals generally transform, before melting, into a more stable solid during heating. Here, it is illustrated that low‐temperature crystals can, however, be melted via fast differential scanning calorimetry (FDSC), even in metallic systems where nucleation and growth kinetics are rapid. For a Au–Si eutectic all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Upon heating, the DSC curve shows a signal with T onset = 495(10) K ( Figure S1 ). In agreement with ref ( 22 ), this signal corresponds to the start of decomposition of Au 4 Si and formation of Au, although in situ heating experiments with synchrotron radiation (DESY, Hamburg, Germany) revealed that very high-quality crystals of Au 4 Si withstand temperatures of up to 573 K for ∼4 min. At T onset = 635(10) K, an endothermic effect with a corresponding signal in the cooling curve is observed, in line with the T e of the eutectic mixture.…”
supporting
confidence: 89%
“…Upon heating, the DSC curve shows a signal with T onset = 495(10) K ( Figure S1 ). In agreement with ref ( 22 ), this signal corresponds to the start of decomposition of Au 4 Si and formation of Au, although in situ heating experiments with synchrotron radiation (DESY, Hamburg, Germany) revealed that very high-quality crystals of Au 4 Si withstand temperatures of up to 573 K for ∼4 min. At T onset = 635(10) K, an endothermic effect with a corresponding signal in the cooling curve is observed, in line with the T e of the eutectic mixture.…”
supporting
confidence: 89%
“…The annealing twins and shrinkage cavities formed in Au nano-film could be attributed to the effect of non-uniform high surface tensions, which is similar with the intrinsic stress induced by high strain rolling in metals with low stacking fault energy [16]. During the annealing, the contents of Si atoms solid dissolved into Au nano-film close to the Au/Si interface dominated the number and size of Au-Si eutectics at Au/Si interfaces [17]. The ripening process of Au nano-film provides the opportunity to weld Au nano-film with Si substrate through the formation of Au-Si eutectic.…”
Section: Resultsmentioning
confidence: 80%
“…18 In recent years, although some theoretical studies reported possible alloy structures of Au-Si, [19][20][21] the local ordering of Au-Si BMG is still lacking. Interestingly, two-dimensional (2D) crystallization was observed at the surface of Au-Si metallic glass, 22,23 which has been experimentally confirmed to be an ordered rectangular structure 22 with the proposed Si-Si bond on the surface. Shpyrko and co-workers 22 claimed that the Au-Si surface ordering was induced by surface-induced freezing, 24 but the ordered prefreezing surface will only appear near the transition temperature rather than a wide range of temperatures, inconsistent with the case of Au-Si.…”
Section: Introductionmentioning
confidence: 89%